Improved Point Dipole Model for Subwavelength Resolution Scattering Near-Field Optical Microscopy (SNOM) - Guizhen Lu; Ruiqi Zhao; Hongcheng Yin; Zhihe Xiao; Jing Zhang (International Journal of Antennas and Propagation)
High-resolution microscopy technique is of significant importance for studying nanomaterials. It is necessary to understand the near-field interaction between the probe and substrate materials in order to get the fine structure of the nanomaterial in the subwavelength scale. The numerical methods such as FDTD, FEM, and MoM are inefficient for the SNOM problems because of the illness of the impedance matrix. The analytic method can only be used for some simple objects such as sphere. Here, a quasianalytical method is developed, in which the analytic formula is refined to adapt to various shapes of the probe approaching the curve of SNOM. By this way, it is helpful in comparing the performance of different probes and giving us a direction to design a new type probe in SNOM. As an application, the developed method is used to study the contrast in the SNOM for the interface between the two different surfaces that have different materials and topography.